Late Holocene climate variability on the eastern flank of the Patagonian Andes (Chile): A δ18O record from mollusks in Lago Cisnes (47°S). (August 2015) - Álvarez, Denisse; Fagel, Nathalie; Araneda, Alberto; Jana-Pinninghoff, Patricia; Keppens, Edward; Urrutia, Roberto
Stable isotopes in mollusk shells have been widely used for hydrological balance reconstructions. However, their use is restricted to lakes that preserve the calcareous material of the shells. Lago Cisnes is located in Patagonia (47°S) and shows a continuous record of three species of mollusk during the past 5000 years. The isotopic records of δ 18 O in Pisidium sp., Lymnaea sp., and Biomphalaria sp. show discrepancies among them, which can be explained by the differential effect that evaporation has on the habitat where each species lives. Between 1800 and 500 cal. yr BP, the three species show similar isotopic variations, suggesting that climatic condition affecting in the same way the different microhabitats in the lake. Around 1700 cal. yr BP, an enrichment of 18 O on mollusks shells indicates drier conditions that prevails until 1100 cal. yr BP. Later on, isotopic signal tends to decrease, suggesting a humid period between 750 and 500 cal. yr BP. Such humid conditions lasted until 170 cal. yr BP, which were evidenced only by Biomphalaria sp. and Pisidium sp. Climate variability during the late Holocene in Lago Cisnes is in agreement with marine records from northern Patagonia, which would suggest westerlies weakening during a northward migration after 1100 cal. yr BP and/or an important temperature control on the evaporation, where low temperatures could decrease the evaporation driven by the westerlies. Additional records in this area would be requested to clarify the westerlies effects on the east flank of the Andes.